Praktik Mudharabah Muqayyadah pada Pembiayaan Pertanian Padi pada P3KPI Al-Zaytun Gantar Indramayu - Mubaroq, Fikri Faiz; Maulana, Rizal (Melati Institute, 2024)
Rice is a staple food for most Indonesians and is also one of the main export agricultural commodities. Based on Indonesia's GDP report, the contribution of the agricultural sector to national income (GDP) has declined over the years, from 24.8% in 1980, 19.4% in 1990, to 14.4% in 2012. In addition, agricultural businesses in the villages are still lacking in terms of capital strengthening because there are not many formal institutions that provide loans to farmers. Paguyuban Petani Penyangga Ketahanan Pangan Indonesia (P3KPI) has a goal stated in its Articles of Association to realize Indonesia's food security. The purpose of this research is to examine the practice of mudharabah muqayyadah in rice farming financing. The research method is a qualitative approach. In this study, 2 resource persons from the Indonesian Islamic Boarding School Foundation and 8 respondents who cultivate agricultural land owned by YPI, namely P3KPI members, were taken. After the data collection process is complete, the collected data will be analyzed systematically. The results show that the practice of mudharabah financing at P3KPI Al-Zaytun involves signing an MoU, where farmers work on nursery activities, land cultivation, planting, fertilizing, spraying, and harvesting, then farmers apply for financing in writing to the Foundation. The foundation checks the results of the work and the supervisor signs the submission, then the funds come down from finance. It is concluded that P3KPI Al-Zaytun has carried out a mudharabah muqayyadah contract on rice crop agricultural financing in accordance with the established regulations and P3KPI Al-Zaytun has carried out alternative solutions to obstacles and defaults properly.